The Cephalometrıc Evaluatıon Of Dental And Soft Tıssue Effects Of Frankel 2 (Fr2) And Headgear Applıances On Class Iı, Dıvısıon 1 Malocclusıon - İlken Karatan Kocadereli (Turkish Journal of Orthodontics, 1992)

(untitled)
The aim of this studg was the cephalometric evaluation of the dental and soft tissue effects of Frankel 2 (FR2) and headgear appliances on Class II, Division 1 malocclusion. 15 of the patients who were in growth and development period used FR2 appliance and 14 of them used combined headgear. 12 patients were the control group and done nothing as treatment during the control period. From all of the patients lateral cephalometric film, was taken at the initial stage and approximately one year later. The FR2 and the headgear appliances had tilted the upper incisors to palatally. Comparing with the headgear group, this tilting effect was more in FR2 group. Besides; with the use of the FR2 appliance the lower incisors moved labiallg significantlg. The lower lip came forward and the profile which was convex became straight. The treatment of the Angle Class II, Division 1 malocclusion with the use of FR2 and headgear appliances was achieved bg dental changes also.